Valor prognóstico dos polimorfismos funcionais nos genes da PON1, TNF-a e TGF-ß no carcinoma de células escamosas oral e orofaríngeo - Santana, Ingrede Tatiane Serafim (2018)
Oral and oropharyngeal squamous cell carcinoma (OOSCC) is a malignant neoplasm of epithelial origin that accounts for 90 to 95% of tumors in oral cavity. Alcohol and tobacco consumption are main risk factors, but the formation of reactive oxygen species (ROS) and presence of chronic inflammatory processes have been shown to favor the carcinogenesis process. Human serum paraoxonase 1 (PON1) is a protein with an important antioxidant action and prevents oxidative stress induced by ROS, in turn, high levels of tumor necrosis factor-alpha (TNF-α) and transforming growth factor-beta (TGF-β) are commonly found in inflammatory processes, and changes in these proteins have been related to development of different neoplasms. Present study aims to investigate the prognostic value of functional polymorphisms in PON1, TNF-α and TGF-β genes in OOSCC. This is a prospective cohort study with patients attended at the Advanced Oncology Center of the North-Riograndense League against Cancer. Data collection of clinical variables was done through the form: gender, age, tumor site, TNM (primary tumor, regional nodule and distant metastasis) classification, clinical stage; and through interview: smoking habits and alcohol intake by the patient. A total of 163 samples from patients with OOSCC and 146 control samples were genotyped by real-time PCR. It was observed that 76.1% of the population was males, 84% older than 52 years, with a more frequent intra-oral clinical presentation (53.4%), in the tongue region (21.5%), tumors greater than 4cm (56.45%), presence of nodal involvement (58.9%) and stages III and IV (79.15%). There was a positive association between drinking and smoking habits in patients with OOSCC and between clinical stage and tumor site (p <0.05). The polymorphisms were in Hardy-Weinberg equilibrium, with exception of rs662 of PON1. TNF-α wild-type GG homozygous genotype (rs1800629) was associated with intra-oral lesions, clinical stage of the most advanced disease (III and IV), and decreased overall disease survival, whereas the polymorphic AA genotype was associated with lip lesion, clinical stage I and II and a longer overall disease survival (p <0.05). It was observed association of TGF-β polymorphic AG and AA genotypes (rs1800469) with larger diameter tumors (T3 and T4) (p <0.05). Finally, the polymorphic TT genotype of PON1 (rs662) in recessive model was associated with a shorter disease survival time within threshold of significance (p = 0.05). In view of the findings, it is suggested that wild-type GG homozygous genotype of TNF-α rs1800629 and TGF-β rs1800469 polymorphic AG and AA genotypes may exert an influence on more aggressive biological behavior of OOSCC and that AG genotype of TNF-α rs1800629 and TT genotype of PON1 rs662 could be prognostic markers in OOSCC. In the clinical practice of oncology, these genotypes can be used to perform early diagnosis, knowledge of the biological behavior of the tumor and choice of appropriate individualized therapy